A rapid electrophoretic method for the detection of serum Lp(a) lipoprotein - Kawakami, Keiko; Tsukada, Atsuko; Okubo, Minoru; Tsukada, Toshihiko; Kobayashi, Tetsuro; Yamada, Nobuhiro; Murase, Toshio (Clinica Chimica Acta, 1989)
A rapid electrophoretic method detecting serum lipoprotein(a) (Lp(a)) was described. When serum lipoproteins were electrophoresed using an agarose gel film containing 0.6% agarose and 3% sucrose, a distinct extra-band was frequently detected between beta- and prebeta-bands. This lipoprotein band was identified as Lp(a) by immunoblotting technique using anti-Lp(a) serum. Using this electrophoretic method, we studied 1353 subjects with a variety of diseases. The Lp(a)-positive subjects accounted for 8.4% of all. Neither sex nor age influenced the frequency of Lp(a) positivity. Frequencies of definite myocardial infarction in Lp(a)-positive subjects did not differ significantly from those in Lp(a)-negative ones. Those of cerebral infarction in Lp(a)-positive subjects were significantly higher than those in Lp(a)-negative ones. An electrophoretic method described herein is very useful for the rapid detection and screening of Lp(a), and hence for large-scale clinical studies of atherosclerotic risk assessment.